2023
DOI: 10.3390/ijerph20053938
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization, Electricity Consumption and Carbon Emissions—Evidence from Manufacturing Industries in China

Abstract: The development of China’s manufacturing industry is constrained by factors such as energy and resources, and low-carbon development is arduous. Digitalization is an important method to transform and upgrade traditional industries. Based on the panel data of 13 manufacturing industries in China from 2007 to 2019, a regression model and a threshold model were used to empirically test the impact of digitalization and electricity consumption on carbon emissions. The research results were as follows: (1) The digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Furthermore, the digital industry’s strategic application of elements like 5G and artificial intelligence fosters the development of new industries that align with current development concepts. This, in turn, supports the transformation of the industrial structure into forms that are environmentally friendly and technology-intensive [ 46 ], as well as the reduction of carbon emissions associated with urban areas.…”
Section: Policy Background and Theoretical Mechanism Analysismentioning
confidence: 83%
“…Furthermore, the digital industry’s strategic application of elements like 5G and artificial intelligence fosters the development of new industries that align with current development concepts. This, in turn, supports the transformation of the industrial structure into forms that are environmentally friendly and technology-intensive [ 46 ], as well as the reduction of carbon emissions associated with urban areas.…”
Section: Policy Background and Theoretical Mechanism Analysismentioning
confidence: 83%
“…On the other hand, resilient companies typically prefer to establish diverse and inclusive work environments. This includes adopting inclusive strategies in recruitment and promotion, ensuring that all employees can participate and benefit, helping achieve sustainable employment and eliminating inequality in employment [2,56,57]. Moreover, resilient enterprises typically place a high priority on social responsibility and sustainable development.…”
Section: Enterprise Resilience and Sustainable Employmentmentioning
confidence: 99%
“…In optimizing industrial structures, DT has continuously penetrated the service industry, becoming a new engine of service trade and promoting the formation of new green industries. The integrated development of emerging and traditional industries based on data elements and the application and promotion of DT in production practice will promote the transformation of industrial structures into technology-intensive and environment-friendly forms (Zhang and Wang, 2023). Choi (2010) used panel data from 151 countries to investigate the impact of the Internet on service trade and found that the digital economy improved the "non-long-distance trade" of traditional services with the help of DT and information technology and promoted the rapid development of service trade.…”
Section: Impact Of Digital Technology On Carbon Emissionsmentioning
confidence: 99%